Complex coacervation of carboxymethyl konjac glucomannan and ovalbumin and coacervate characterization. Issue 13 (3rd November 2022) - Cao, Ya-Qian; Huang, Guo-Qing; Li, Xiao-Dan; Guo, Li-Ping; Xiao, Jun-Xia
Abstract: Carboxymethyl konjac glucomannan (CMKGM) is an anionic derivative of konjac glucomannan (KGM). Its coacervation with ovalbumin (OVA) was investigated through turbidity and coacervate yield measurements and the resultant CMKGM-OVA coacervates were characterized as a function of phase separation pH. The results indicated that CMKGM could coacervate with OVA in pHs ranging from 2.0 to 4.5. OVA to CMKGM mass ratios higher than 1:1 led to insoluble coacervates, while lower ratios conferred soluble complexes. NaCl suppressed the interaction between CMKGM and OVA and could resuspend their precipitated coacervates. The interaction between the two polyelectrolytes was not affected in temperatures ranging from 25 °C to 55 °C, but was weakened in higher temperatures. The coacervation increased the thermal stability and induced structural changes in both the polyelectrolytes. Atomic force microscope observation revealed that the CMKGM-OVA coacervates separated in mass ratio 1:1 was not susceptible to aggregation, and quartz crystal microbalance with dissipation analysis demonstrated that OVA exhibited the strongest absorption towards CMKGM in pH 3.0 in multilayer mode. Hence, CMKGM is a promising polyelectrolyte for coacervation with proteins and could be used in the construction of targeted delivery systems through the electrostatic interaction with oppositely charged biopolymers. Graphical Abstract: UF0001